Agroecological Aspects of Black Pepper (Piper nigrum L.) Cultivation in Kerala: A Review - Sasikumar, B.; Kumar, B. Mohan; Kunhamu, T. K. (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
Black pepper is a very important spice and medicinal crop of India. The country produces about 62,000 metric tonnes of black pepper annually, of which 10â€“12% is exported. Kerala with an area of 82,761 ha under the crop is a leading producer of the spice in India. It is grown under varied agro-ecologies in the state ranging from sea-level to High Ranges. The crop, a climber, is cultivated either as a monocrop trailed on different multipurpose support trees (called â€œstandardsâ€, e.g. Ailanthus triphysa, Erythrina indica, Garuga pinnata, Gliricidia sepium etc.) or in the homesteads along with assorted trees like Areca catechu, Cocos nucifera, Artocarpus heterophyllus, Mangifera indica and the like. Trailing a sciophytic (shade-loving) climber on woody perennial support trees makes it a unique agronomic system and an excellent example of agroforestry. Attractive prices, albeit fluctuations, long shelf-life of the produce, and the ability to provide a range of ecosystem services including supporting and regulatory services (e.g. carbon sequestration and soil fertility enrichment), make black pepper production an attractive land use option in Kerala. This paper reviews the literature on agroecology of the crop with particular reference to Kerala.